Answer:
![\large\boxed{1](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B1%3Cx%3C7%5Cto%20x%5Cin%281%2C%5C%207%29%7D)
Step-by-step explanation:
![|x-4|](https://tex.z-dn.net/?f=%7Cx-4%7C%3C3%5Ciff%20x-4%3C3%5C%20%5Cwedge%5C%20x-4%3E-3%5Cqquad%5Ctext%7Badd%204%20to%20both%20sides%7D%5C%5C%5C%5Cx%3C7%5C%20%5Cwedge%5C%20x%3E1%5CRightarrow1%3Cx%3C7)
<span>6. 9 + 11y – y2 + y3 – 4y4
This expression has 5 terms.
7. </span><span>(2a + 3b) + 4c = 2a + (3b + 4c)
Associative property of addition, because you're moving the parentheses.
</span><span>
8. </span><span>If m = 4 and n = 4, then m = n
Substitution property.
9. </span><span>-9 + 5 – (-2) + 17
-4 - (-2) + 17
-2 + 17
15
10. </span><span>- 35 - (- 13 )
-22
11. -40 + 23 - 19 + 31
-17 - 19 + 21
36 + 21
57
12.</span><span> (-2)³
-2 * -2 * -2
-8
13. - 925
14. </span><span>15(3y – 5)
45y - 75
15. (7 + 6w)6
42 + 36w
16. </span><span>3n+57
17. 9p-63</span>
Answer:
2&7
Step-by-step explanation:
Answer:
I don't know sorry
it is clear that this is not online class
Let first consider the equations one by one and will be solving one by one ;
![{:\implies \quad \sf x+\dfrac{1}{y}=4}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Csf%20x%2B%5Cdfrac%7B1%7D%7By%7D%3D4%7D)
Multiplying both sides by y will lead ;
![{:\implies \quad \sf xy+1=4y}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Csf%20xy%2B1%3D4y%7D)
![{:\implies \quad \boxed{\sf xy=4y-1\quad \cdots \cdots(i)}}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Cboxed%7B%5Csf%20xy%3D4y-1%5Cquad%20%5Ccdots%20%5Ccdots%28i%29%7D%7D)
Now, consider the second equation which is ;
![{:\implies \quad \sf y+\dfrac{1}{x}=\dfrac14}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Csf%20y%2B%5Cdfrac%7B1%7D%7Bx%7D%3D%5Cdfrac14%7D)
Multiplying both sides by x will yield
![{:\implies \quad \sf xy=\dfrac{x}{4}-1}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Csf%20xy%3D%5Cdfrac%7Bx%7D%7B4%7D-1%7D)
![{:\implies \quad \boxed{\sf xy=\dfrac{x-4}{4}\quad \cdots \cdots(ii)}}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Cboxed%7B%5Csf%20xy%3D%5Cdfrac%7Bx-4%7D%7B4%7D%5Cquad%20%5Ccdots%20%5Ccdots%28ii%29%7D%7D)
As LHS of both equations (i) and (ii) are same, so equating both will yield;
![{:\implies \quad \sf 4y-1=\dfrac{x-4}{4}}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Csf%204y-1%3D%5Cdfrac%7Bx-4%7D%7B4%7D%7D)
Multiplying both sides by 4 will yield
![{:\implies \quad \sf 16y-4=x-4}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Csf%2016y-4%3Dx-4%7D)
![{:\implies \quad \sf 16y=x}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Csf%2016y%3Dx%7D)
Dividing both sides by y will yield :
![{:\implies \quad \boxed{\bf{\dfrac{x}{y}=16}}}](https://tex.z-dn.net/?f=%7B%3A%5Cimplies%20%5Cquad%20%5Cboxed%7B%5Cbf%7B%5Cdfrac%7Bx%7D%7By%7D%3D16%7D%7D%7D)
<em>Hence, the required answer is 16</em>